2020
DOI: 10.1001/jamadermatol.2020.1406
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Abrocitinib in Patients With Moderate-to-Severe Atopic Dermatitis

Abstract: an oral, once-daily Janus kinase 1 selective inhibitor, was effective and well tolerated in a phase 3 monotherapy trial of patients with moderate-to-severe atopic dermatitis (AD). OBJECTIVE To investigate the efficacy and safety of abrocitinib in adolescents and adults with moderate-to-severe AD in an identically designed trial. DESIGN, SETTING, AND PARTICIPANTS This phase 3, double-blinded, placebo-controlled, parallel-group randomized clinical trial included patients 12 years or older with a clinical diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
325
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 279 publications
(374 citation statements)
references
References 35 publications
13
325
2
4
Order By: Relevance
“…abrocitinib, baricitinib, and upadacitinib) and injectable anti-IL-13 antibodies (i.e. tralokinumab and lebrikizumab) that have shown promise in early-phase clinical studies [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…abrocitinib, baricitinib, and upadacitinib) and injectable anti-IL-13 antibodies (i.e. tralokinumab and lebrikizumab) that have shown promise in early-phase clinical studies [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…At week 12, 43.8%, 23.7%, and 7.9% of those participants receiving 200 mg abrocitinib, 100 mg abrocitinib, and placebo, respectively, achieved an IGA response in the JADE-MONO-1 study, 18 whereas the IGA response was 38.1%, 28.4%, and 9.1%, respectively, in the JADE MONO-2 trial. 19 According to the JADE MONO-1 study, an improvement of at least 75% in EASI score (EASI-75) was reached in 62.7%, 39.7%, and 11.8% of those treated with 200 mg, 100 mg, and placebo, respectively, whereas EASI-75 was achieved in 61.0%, 44.5%, and 10.4% of participants receiving 200 mg, 100 mg, and placebo, respectively, in the JADE MONO-2 study. At week 12, a Peak Pruritus Numerical Rating Scale score improvement of 4 or more was achieved in 57%, 38%, and 15% of those participants receiving 200 mg abrocitinib, 100 mg abrocitinib, and placebo, respectively, in the JADE MONO-1 study and in 55.3%, 45.2%, and 11.5% of participants in the JADE MONO-2 study.…”
Section: Efficacy Of Jak Inhibitors In Admentioning
confidence: 99%
“…TEAEs were reported in 77.9%, 69.2%, and 57.1% of the 200 mg abrocitinib, 100 mg abrocitinib, and placebo groups, respectively. According to the JADE MONO-2 study, 19 of 391 subjects, SAEs were reported in 1.3%, 3.2%, and 1.3% of patients in the 200 mg abrocitinib, 100 mg abrocitinib, and placebo groups, respectively, with one sudden cardiac death reported in the 100 mg abrocitinib group occurring during the follow-up period and was deemed not to be related to treatment. TEAEs were reported in 65.8%, 62.7%, and 53.8% of patients in the 200 mg abrocitinib, 100 mg abrocitinib, and placebo treatment arms, respectively.…”
Section: Safety Of Jak Inhibitors In Admentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 A phase II randomized, double-blind, placebo-controlled trial assessed the safety and the efficacy of abrocitinib in AD patients via improvement in IGA scores, with a focus on the proportion of patients achieving IGA scores of 0 or 1 (clear or almost clear skin). 44 46 The results of these trials suggest the most efficacious dosing for abrocitinib is either 100 mg or 200 mg oral tablets once daily. 42,45,47…”
Section: Efficacy Of Oral Jak Inhibitors For Treatment Of Ad Abrocitinibmentioning
confidence: 99%